The Effect of Board Diversity on Corporate Innovation: A Study on Canadian Firms - Abtahi, Zahra (Université d'Ottawa / University of Ottawa, 2021)
This research investigates the association between board diversity and firms’ innovation in Canada over the period of 2001 to 2015. Previous research revealed that board diversity has conflicting effects on the firm innovation depending on the country, and there is no such study conducted in Canada. Moreover, only few proxies for the board diversity have been used to study the subject in the literature. Thus, this study introduces new factors of board diversity and add to the literature by assessing the topic in Canadian firms. We found that firms with more women on the board when women members are more than one fourth of the board members can increase the number of patents. Also, while more education diversity results in more patent numbers, more diversity in the number of years that board members have served the board results in less patent numbers for the firms, it is noteworthy that there is no significant association between the deviation in the number of years that board members have served the company and the innovation of the firm.
Keywords: Innovation; R&D expenses; Patent; Citation; Canada; Board Diversity; Corporate Governance